Caught in the middle : - Garrity, Carla B. (Jossey-Bass, 1997)
That their parents' divorce adds to the burden of children's growing up is amply documented by Garrity and Baris, child psychologists in Denver who specialize in treating partners of acrimoniously failed marriages. Their book is designed to help parents and the professionals who work with them arrive at solutions to stressful situations that will enable the children of divorce to grow into emotionally healthy adults. Interparental conflict affects children at all ages, but, the authors contend, children under five are especially vulnerable, while older children more often join in the conflict by taking sides. The authors' remediation model for containing, regulating and resolving anger is presented for use by attorneys, mental health professionals and divorced parents to shape an effective co-parenting plan that does not make pawns of children